Proceedings of the 6th Workshop on Representation Learning for NLP (RepL4NLP-2021) 2021
DOI: 10.18653/v1/2021.repl4nlp-1.3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension Based Question Answering using Bloom’s Taxonomy

Abstract: Current pre-trained language models have lots of knowledge, but a more limited ability to use that knowledge. Bloom's Taxonomy helps educators teach children how to use knowledge by categorizing comprehension skills, so we use it to analyze and improve the comprehension skills of large pre-trained language models. Our experiments focus on zero-shot question answering, using the taxonomy to provide proximal context that helps the model answer questions by being relevant to those questions. We show targeting con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Bloom's taxonomy is used by educational institutions to design course learning outcomes (CLOs) and match assessment items to them in order to improve student learning (Shaikh, Daudpott & Imran, 2021). However, difficulties in using the taxonomy have been reported and some authors have suggested that there are inherent flaws in the classification system (Sahu et al, 2021). To address this issue, researchers have proposed deep learning models such as LSTM-based models to more accurately classify CLOs and assessment items into Bloom's levels (Waheed et al, 2021).…”
Section: What Is a Taxonomy? What Are Txonomies In Education?mentioning
confidence: 99%
See 2 more Smart Citations
“…Bloom's taxonomy is used by educational institutions to design course learning outcomes (CLOs) and match assessment items to them in order to improve student learning (Shaikh, Daudpott & Imran, 2021). However, difficulties in using the taxonomy have been reported and some authors have suggested that there are inherent flaws in the classification system (Sahu et al, 2021). To address this issue, researchers have proposed deep learning models such as LSTM-based models to more accurately classify CLOs and assessment items into Bloom's levels (Waheed et al, 2021).…”
Section: What Is a Taxonomy? What Are Txonomies In Education?mentioning
confidence: 99%
“…To address this issue, researchers have proposed deep learning models such as LSTM-based models to more accurately classify CLOs and assessment items into Bloom's levels (Waheed et al, 2021). In addition, Bloom's taxonomy was used to analyze and improve the comprehension skills of the pre-trained language models, resulting in improved performance on question answering tasks (Sahu et al, 2021).…”
Section: What Is a Taxonomy? What Are Txonomies In Education?mentioning
confidence: 99%
See 1 more Smart Citation